Professional soccer players perceptions of the English Football Association 4 corner model in supporting first team transitions - Diouf, M.; Miller, J.; Rothwell, M. (Journal of Sports Sciences, 2024)
The English Football Association (FA from hereon in) 4 Corner Model is a multidisciplinary framework that aims to enhance player talent identification and development, and is characterised by physical, social, technical/tactical and psychological components. Despite the framework being prominent within English football development pathways, player insights into the effectiveness of the framework in supporting academy to first team transitions are lacking. Therefore, the aim of this study was to explore established first team professional footballer`s perceptions of the FA 4 Corner Model, in relation to the attributes that they perceived to facilitate the successful transition to a professional first team environment. Twelve current (n = 8) and ex (n = 4) professional players who had successfully transitioned from a youth academy, and subsequently became an established first team player, were interviewed for the study. Interpretations across the qualitative data set highlighted the importance of players adapting to physical and tactical demands, while also dealing with different psychosocial factors when entering a first team setting. The study highlights that disparities can exist between players, coaches, practitioners, and sport scientists perceived development needs, a situation that could hinder players progression through the player pathway.